Entangled systems : - Audretsch, Jurgen (Wiley-VCH, 2007)
This is an introductory textbook for advanced students of physics, chemistry and computer science, covering an area of physics that has lately witnessed rapid expansion. The topics treated here include quantum information, quantum communication, quantum computing, teleportation and hidden parameters, thus imparting not only a well-founded understanding of quantum theory as such, but also a solid basis of knowledge from which readers can follow the rapid development of the topic or delve deeper into a more specialized branch of research. Commented recommendations for further reading as well as end-of-chapter problems help the reader to quickly access the theoretical basics of future key technologies - BOOK JACKET.